High-Dose Diazepam Controls Severe Dyskinesia in Anti-NMDA Receptor Encephalitis. Issue 4 (August 2021) - Shin, Hye-Rim; Jang, Yoonhyuk; Shin, Yong-Won; Chu, Kon; Lee, Sang Kun; Lee, Soon-Tae
Abstract : Objective: Because there is no standard treatment to control dyskinesia in anti-NMDA receptor (NMDAR) encephalitis, we analyzed the therapeutic efficacy of high-dose diazepam in dyskinesia associated with NMDAR encephalitis. Methods: We reviewed patients with NMDAR encephalitis with dyskinesia who were admitted to Seoul National University Hospital between November 2012 and July 2018. High-dose diazepam was administered orally or via a nasogastric tube 3–6 times a day. We assessed the treatment effect by comparing dyskinesia severity between the first day of the highest dose of diazepam and one week after the treatment. Results: Among 68 patients with NMDAR encephalitis during the study period, 33 patients were treated with enteral diazepam (ranging from 6 to 180 mg) to control dyskinesia, along with immunotherapy. The severity of dyskinesia improved from average grade 2.4 ± 0.6 to 1.1 ± 0.7 after 1 week of the highest dose of diazepam (mean severity change −1.4 ± 0.6, 95% confidence interval −1.2 to −1.6; p < 0.001). No patients had serious adverse events except for mild sedation. Conclusions: Dyskinesia in NMDAR encephalitis improved after treatment with enteral diazepam without significant side effects. This study suggests that enteral diazepam could be a treatment option for control dyskinesia in NMDAR encephalitis. Classification of Evidence: This study provides Class IV evidence that for patients with dyskinesias associated with NMDAR encephalitis, enteral diazepam is effective and safe in dyskinesia control.